Strengthening Religious Moderation In Multicultural Indonesia: A Descriptive Study In East Nusa Tenggara And Bali - Amran, Ali; Fikri, Sholeh; Siregar, Budi Gautama; Abd Ghafar bin Don; Nasution , Syafri Martabe Rizka (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to analyse the understanding and implementation of religious moderation in maintaining harmony among diverse groups and strengthening national unity and integrity in a multi-ethnic society, with a focus on the regions of East Nusa Tenggara and Bali. This research employed descriptive qualitative methods, collecting data through observation, documentation, and interviews. Data triangulation techniques were then used to analyse the data systematically. Additionally, during data analysis, the author used the VosViewer application to track previous research related to the discussed themes. The results showed that the people of East Nusa Tenggara and Bali generally had a good understanding of religious moderation. Various efforts and strategies to promote religious moderation had been implemented, yielding positive results that needed to be sustained, especially in the context of multiethnic societies. However, intolerant attitudes were still found in some areas, especially towards Muslims who are in a minority position in Kupang and some places in Bali. This finding confirms the importance of strengthening multiculturalism-based religious moderation programmes to build social harmony amid the nation's plurality.